Strength and damage growth in composite bonded joints with defects - Ribeiro, F.M.F. (2016)
The use of adhesive joints is increasing in various industrial applications because of their advantages such as weight reduction, reduction of stress concentrations and ease of manufacture. However, one of the limitations of adhesive joints is the difficulty in predicting the joint strength due to the presence of defects in the adhesive. This paper presents an experimental and numerical study of single-lap joints (SLJ) with defects centred in the adhesive layer for different overlap lengths (LO) and adhesives. The numerical analysis by cohesive zone models (CZM) included the analysis of the peel (σy) and shear (τxy) stress distributions in the adhesive layer, the CZM damage variable study and the strength prediction. The joints’ behaviour was accurately characterized by CZM and showed a distinct behaviour as a function of the defect size, depending on the adhesive.